Reconsidering Confederation Canada's Founding Debates, 1864-1999 - Heidt, Daniel (University of Calgary Press, 2018)
July 1st 1867 is celebrated as Canada's Confederation - the date that Canada became a country. But 1867 was only the beginning. As the country grew from a small dominion to a vast federation encompassing ten provinces, three territories, and hundreds of First Nations, its leaders repeatedly debated Canada's purpose, and the benefits and drawbacks of the choice to be Canadian. Reconsidering Confederation brings together Canada's leading historians to explore how the provinces, territories, and Treaty areas became the political frameworks we know today. In partnership with The Confederation Debates, an ongoing crowdsourced, non-partisan, and non-profit initiative to digitize all of Canada's founding colonial and federal records, this book breaks new ground by integrating the treaties between Indigenous peoples and the Crown into our understanding of Confederation. Rigorously researched and eminently readable, this book traces the unique paths that each province and territory took on their journey to Confederation. It shows the roots of regional and cultural grievances, as vital and controversial in early debates as they are today. Reconsidering Confederation tells the sometimes rocky, complex, and ongoing story of how Canada has become Canada.